Fundamentals of HIV biology - Simon, Viviana (Henry Stewart Talks, 2020)
HIV infections worldwide and in USA, Origins of HIV-1 and HIV-2, HIV transmission, HIV pathogenesis and treatment, HIV-1 morphology, The HIV genome, The HIV life cycle, Unique features of retroviruses, Principles of HAART, Prophylaxis, HIV entrance into the cell, Intracellular immune defenses, The challenge to cure HIV/AIDS